Constellation Estimation, Coherent Signal Processing, and Multiperspective Imaging in an Uncoupled Bistatic Cooperative Radar Network - Fenske, Patrick; Kögel, Tobias; Ghasemi, Roghayeh; Vossiek, Martin (IEEE Journal of Microwaves, 2024)
Cooperative radar networks are a promising technology in various areas, such as vehicle-to-infrastructure networks for automotive radar and radar remote sensing with UAVs. The use of widely distributed radar networks enables the detection of targets with complex scattering characteristics, as their coherent bistatic images are superior for forward scattering, and each monostatic image illuminates a scene from a different perspective. This work introduces a signal processing scheme that addresses two main challenges in this area: the coherent signal processing of uncoupled radar nodes and the self-localization of the nodes for radar image combination. A comprehensive signal model that incorporates time, frequency and phase incoherency is introduced. Based on this, an algorithm for constellation estimation, synchronization up to the carrier phase level, and multiperspective imaging is developed. The proposed approach is experimentally verified using commercially available 77GHz single-input/multiple-output radar nodes. The measurements for different radar constellations and various target scenes show a self-localization accuracy below 6cm in range and below 2.5∘ for the incident angles. The resulting images of various scenes clearly indicate an information gain compared to single monostatic images due to the combination of bistatic and multiperspective monostatic images.<br
Keywords: Radar; Radar imaging; Phase noise; Radar antennas; Chirp; Time-frequency analysis; Synchronization; Bistatic radar; chirp sequence modulation; cooperative radar networks; FMCW; localization; millimeter-wave radar; multiperspective imaging; radar networks; synchronization

Integrated Self-Contained Trajectory Estimation and Multistatic SAR Imaging in a Non-Static Uncoupled Bistatic Radar Network - Fenske, Patrick; Kögel, Tobias; Ghasemi, Roghayeh; Gunders-Hunt, Danielle; Vossiek, Martin (IEEE Journal of Microwaves, 2025)
Radar imaging performance can be significantly improved by creating synthetic apertures along a radar sensor's trajectory compared to standard MIMO imaging radars. Additionally, observing the scenery from both monostatic and bistatic perspectives with large bistatic angles can further increase the information content of radar images, as different parts of complex targets can exhibit different scattering mechanisms. Both technologies, synthetic aperture radar and coherent multistatic radar networks, come with demanding system requirements regarding the localization and synchronization of the involved radars, which are addressed by the proposed approach. The unique aspect of our novel bi-/multistatic radar approach is that no auxiliary sensor technology is needed to determine the trajectory. The same radar signals are jointly used at the same time for trajectory determination, clock synchronization, and bistatic SAR imaging. The integrated self-contained trajectory estimation is based on a particle filter algorithm that processes the line-of-sight radar signals of the bistatic radar pairs, which are exchanged in a double-sided two-way ranging manner. This approach opens up new applications of bi-/multistatic radar for autonomous air and ground vehicles. However, the requirement of a line-of-sight connection between the radar pairs imposes a constraint on possible bistatic constellations and trajectories. Therefore, it is shown that suitable compromises regarding the geometry, localization accuracy, and resolution of SAR imaging must also be taken into account. We demonstrate the capabilities of this approach by generating monostatic and bistatic SAR images with 77 GHz SIMO FMCW radar sensors from indoor and outdoor measurement scenarios with synthetically generated apertures estimated by the integrated self-contained localization algorith
Keywords: Bistatic radar; cooperative radar networks; FMCW; localization; multiperspective imaging; SAR; synchronization

Time and Frequency Synchronization for Real-Time Wireless Digital Communication Systems - Ghasemi, Roghayeh; Kögel, Tobias; Fenske, Patrick; Schober, Robert; Vossiek, Martin (2024 15th German Microwave Conference, GeMiC 2024, 2024)
In this paper, we present a fully field-programmable gate array (FPGA)-based real-time implementation of a wireless time and frequency synchronization scheme for communication and sensor networks. For this purpose, a communication link using frequency division multiplexing is established between three distributed stations. This allows the simultaneous and continuous transmission of quadrature phase-shift keying-modulated data between the stations with no interference. The time difference between the stations is estimated using the precision time protocol. Due to the deterministic processing time of the FPGA implementation, precise time synchronization is achieved, with a standard deviation of 10 ns per communication cycle. Moreover, in the proposed method, successive estimates of the time offset are used to estimate the frequency difference between the stations, which allows the tuning of the digitally controlled crystal oscillators of the distributed stations to the frequency of the central reference station, with a clock rate deviation of approximately two parts per billion. The structure is robust with respect to multi path interference and is extendable to additional frequency bands and stations. The results demonstrate the excellent performance and robustness of the proposed concept.
CRIS-Team Scopus Importer:2024-04-26
Keywords: Costas loop; field-programmable gate array (FPGA); Precision Time Protocol (PTP); time and frequency synchronization; wireless communication network; wireless synchronization

Towards Detecting Climate Change Effects With UAV-Borne Imaging Radars - Ullmann, Ingrid; Bonfert, Christina; Grathwohl, Alexander; Lahmeri, Mohamed Amine; Mustieles Perez, Victor; Kanz, Julian; Sterk, Elena; Bormuth, Frederik; Ghasemi, Roghayeh; Fenske, Patrick; Villano, Michelangelo; Schober, Robert; et al. (IEEE Journal of Microwaves, 2024)
Climate change is associated with a variety of environmental phenomena, such as the melting of glaciers, the drying out of crops and soils, and an increase in the risk of avalanches. To detect and monitor these changes, satellite-based radar imaging is widely used, as it enables the large-scale mapping of the Earth's surface independent of weather and sunlight. An emerging field of research is to use radar systems mounted on unmanned aerial vehicles (UAVs) for this purpose. UAV-borne radar systems image smaller areas, but can capture them in greater detail, more flexibly in terms of flight trajectory, and at shorter repetition intervals. This article presents the capabilities of UAV-based radar systems and the associated challenges in terms of system design and imaging techniques for detecting and monitoring the effects of climate change. Current research results are shown. In addition, we give an outlook on using a swarm of cooperative UAVs, each carrying a radar. UAV swarms will enable a higher imaging quality with respect to resolution and detectability, but at the same time come with a number of additional challenges, which will be discussed in the paper as well.
CRIS-Team Scopus Importer:2024-09-27
Keywords: Climate change; microwaves in climate change; radar; radar imaging; remote sensing; UAV

Ultrahigh-Performance Radio Frequency System-on-Chip Implementation of a Kalman Filter-Based High-Precision Time and Frequency Synchronization for Networked Integrated Sensing and Communication Systems - Ghasemi, Roghayeh; Fenske, Patrick; Kögel, Tobias; Hehn, Markus; Ullmann, Ingrid; Vossiek, Martin (IEEE Open Journal of Instrumentation and Measurement, 2025)
The integration of radar sensing and imaging capabilities into future integrated sensing and communication (ISAC) networks enables advanced use cases, including autonomous vehicle navigation, real-time health monitoring, and smart city management. However, ultraprecise time and frequency synchronization is crucial for unlocking the full potential of such networked ISAC systems. In this article, a novel real-time wireless time and frequency synchronization scheme is developed and fully implemented on a high-end radio frequency system-on-chip field-programmable gate array (FPGA) platform. The excellent performance and robustness of the proposed solution in practical applications are demonstrated. It is evidenced that the recursive nature of the Kalman filter is well suited to the dynamic capabilities of FPGA-based simultaneous synchronization. Observed values obtained through the precision time protocol (PTP) are iteratively refined, thus effectively compensating for uncertainties encountered during a synchronization packet exchange. Due to the deterministic processing time inherent in the FPGA, the proposed synchronization method achieves exceptional precision, with clock offset deviations in the nanosecond range and clock rate deviations limited to only a few parts per billion, even across considerable distances between the network node
Keywords: Synchronization; Clocks; Time-frequency analysis; Frequency synchronization; Kalman filters; Sensors; Protocols; Frequency estimation; Wireless sensor networks; Real-time systems